Clinical application of the COVID-19 Reporting and Data System (CO-RADS) in patients with suspected SARS-CoV-2 infection: observational study in an emergency department. Issue 1 (January 2021) - Turcato, G.; Zaboli, A.; Panebianco, L.; Scheurer, C.; Venturini, A.; Tezza, G.; Canelles, M.F.; Ausserhofer, D.; Pfeifer, N.; Wieser, A.
Highlights: CO-RADS improves the risk classification by 65.8% in patients affected by COVID-19. CO-RADS combined with RT-PCR presents an AUC of 0.98 for patients with COVID-19. CO-RADS improves the risk classification by 82.1% in patients not affected by COVID-19.